2009
DOI: 10.1007/s11814-009-0102-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and stability of ethylene polymerization in multizone circulating reactors

Abstract: Multizone circulating bed reactors (MZCR) have the exclusive characteristics of producing polymers of different molecular weights in a single particle. Traditional fluidized bed reactors, on the other hand, can produce only one kind of molecular weight with relatively narrow distribution. A dynamic model for the MZCR is used to illustrate the basic dynamic behavior of the new reactor design used for polyethylene production. The model is used to study the copolymerization of ethylene with butene. Several parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Practically, propylene polymerization manufacture is not operated with high range of reactor temperature oscillation because wide range of polymer properties and hotspots has to be avoided. Nevertheless, temperature oscillation behavior upon increasing catalyst ow rate has also found by Ghasem, 40 Hatzantonis 7 and Hyanek. 41 Several other papers have also indicated this behavior in polyethylene production.…”
Section: Results Based On Phenomenological Modelsupporting
confidence: 54%
See 1 more Smart Citation
“…Practically, propylene polymerization manufacture is not operated with high range of reactor temperature oscillation because wide range of polymer properties and hotspots has to be avoided. Nevertheless, temperature oscillation behavior upon increasing catalyst ow rate has also found by Ghasem, 40 Hatzantonis 7 and Hyanek. 41 Several other papers have also indicated this behavior in polyethylene production.…”
Section: Results Based On Phenomenological Modelsupporting
confidence: 54%
“…The Reynold stress related to turbulent viscosity is estimated from the standard k-3 turbulent model. The turbulent kinetic energy, k, and the turbulent dissipation rate, 3, for phase q are obtained by solving eqn (40) and (41) in Table 3. The solutions of turbulent kinetic energy and turbulent dissipation rate of phase q were used to calculate turbulent viscosity as…”
Section: Mathematical Model Based On Cfdmentioning
confidence: 99%
“…In all of the previous studies on the modeling of PE MZCRs in the literature, 5,[8][9][10] it was assumed that there was a constant solid velocity and bed porosity along the riser and downer. However, we found during this study (shown in this section) that the effect of hydrodynamics was not negligible in the MZCR.…”
Section: Hydrodynamics Of Mzcr (Cold Model)mentioning
confidence: 99%
“…This model is capable of predicting the polymer productivity, particle size distribution, and molecular weight and polydispersity of the polymer. In another study, Ghasem et al 9, 10 extended the model of Fernandez and Lona 5 to the dynamic model so that the transient behavior of the MZCR could be simulated. Moreover, the isothermal condition imposed by Santos et al 8 and Fernandes and Lona 5 was employed in their study.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of solids is approximately equal to 90% in the downer and 40% in the riser . Few studies for the MZCR can still be found, especially those who used CFD tools. Wei et al and Yan et al used the Eulerian–Eulerian approach to simulate one MZCR, but without significant contributions.…”
Section: Introductionmentioning
confidence: 99%